SENTENCE SCRAMBLE GAME: MEDIA PEMBELAJARAN SINTAKSIS PADA ANAK TUNARUNGU TINGKAT SEKOLAH DASAR - Yeni Irma N; Sayidah Alawiyah; Retno Widianti; Tri Dilla A; Aulia Azmi (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
AbstractThis research aims to produce the software of Sentence Scramble Game (SSG)as a syntax learning media for deaf children. Learning syntax includes the discussionabout sentence structures and functional orders. The method employed in this studyis research and development (R D) adopting the model development of Borg Gall,which covers ten steps simplified into six steps, namely: 1) analysis, 2) design, 3)development, 4) expert validation, 5) testing, and 6) disseminations. The subjects inthis research were 7 students of Karnamanohara Type B Special School. The methodsof data collection are direct observation, interview and questionnaires. The data wereanalyzed by descriptively and qualitatively. The results of this research show thatSentence Scramble Games (SSG) are eligible, proven by the results of the materialvalidation test with good category (4.0) and the media expert’s trial results with verygood category (4.2). The assessment of the feasibility of the media is also supportedby the trial results of three persons with excellent categories (4.1). A large scale trialby seven people results in the excellent category (4.6).